Approach to a Substituted Heptamethine Cyanine Chain by the Ring Opening of Zincke Salts - Štacková, Lenka; Štacko, Peter; Klán, Petr (Journal of the American Chemical Society, 2019)
Cyanine dyes play an indispensable and central role in modern fluorescence-based biological techniques. Despite their importance and widespread use, the current synthesis methods of heptamethine chain modification are restricted to coupling reactions and nucleophilic substitution at the meso position in the chain. Herein, we report the direct transformation of Zincke salts to cyanine dyes under mild conditions, accompanied by the incorporation of a substituted pyridine residue into the heptamethine scaffold. This work represents the first general approach that allows the introduction of diverse substituents and different substitution patterns at the C3'-C5' positions of the chain. High yields, functional tolerance, versatility toward the condensation partners, and scalability make this method a powerful tool for accessing a new generation of cyanine derivatives.